Design and SAR computation of two different internal antennas for mobile terminals. (2021) - Kurup, Hrudya B.; M., Remsha; Antony, Divya; Rodrigues, Stephen
Abstract: Low profile antennas are promising candidates in miniaturization-driven applications like mobile and personal communication devices due to their compactness and robustness. However human exposure to radiation in presence of the human body is also an important parameter that needs to be analysed as these devices are now an indispensable part of our day-to-day life. The paper attempts to compute and compare the radiation characteristics and specific absorption rate of two commonly used antennas in mobile terminals – a PIFA and a shorted patch antenna. The two antennas presented in the paper are specifically designed to work in the ISM 2.4 GHz band. The Specific absorption rate values of these antennas are also computed and compared along with other antenna parameters to understand their interaction pattern in the presence of the human body. All simulations presented in the paper are performed using CST Microwave Studio.